Factor Analysis of Willingness to Pay (WTP) for Health Insurance - Rauyani, Rauyani; Adamy, Aulina; Nurjannah, Nurjannah; Fitrianda, Yunita (GLOBAL HEALTH SCIENCE GROUP, 2025)
Aceh People's Health Insurance (JKA) occupies the largest portion of the Special Autonomy Fund in the Health Sector. The decline and expiration of the Special Autonomy Fund will have an impact on financing for JKA (Aceh Health Insurance), even though currently there has been a transition into the JKN-KIS (National Health Insurance-Healthy Indonesian Card) program. However, there are still many people who do not understand this transitional period. This study aims to evaluate the willingness to pay (WTP) to pay for health insurance in the people of Aceh. This research is analytic with a cross-sectional design. The population in this study is all the people of Aceh province. The sampling technique was purposive sampling, amounting to 768 people. Data collection was carried out by sending a google form to the Aceh Regional Secretariat Office group through the Aceh People's Welfare (KESRA) section, which would then be sent to the KESRA group in the Regency/City to be disseminated. Data analysis used multiple logistic regression tests. Multivariate analysis found that low income was the dominant factor determining willingness and ability to pay for health insurance compared to other variables (OR: 7; 95%; p value of 0.001). According to the findings of this study, 509 of 766 (66.3%) respondents were willing to pay for health insurance, with an average willingness to pay Rp. 38,539.